Application of the concept of cost benefits analysis (CBA) to property level flood risk adaptation measures: A conceptual framework for residential. Issue 2 (6th May 2014) - Joseph, Rotimi; Proverbs, David; Lamond, Jessica; Wassell, Peter
Abstract : Purpose: – There has been a significant increase in flooding in the UK over the past ten years. During this time, Government policy has moved from investment in flood defences towards encouraging property owners to take responsibility for reducing the impact of flooding. One of the ways in which this can be achieved is for homeowners to adapt their properties to flood risk by implementing property level flood risk adaptation (PLFRA) measures. While there has been some attempt to develop an understanding of the benefits of such measures, these previous studies have their limitations in that the intangible benefits have not been fully considered. As such, there remains a need for further development of these studies towards developing a more comprehensive understanding of PLFRA measures. It is against this background the purpose of this paper is to present a conceptual cost benefit analysis (CBA) framework for PLFRA measure. This framework brings together the key parameters of the costs and benefits of adapting properties to flood risk including the intangible benefits, which have so far been overlooked in previous studies. Design/methodology/approach: – A critical review of the standard methods and existing CBA models of PLFRA measures was undertaken. A synthesis of this literature and the literature on the nature of flooding and measures to reduce and eliminate their impacts provides the basis for the development of a conceptual framework of the costs and benefits of PLFRA measures. Within the developed framework, particular emphasis is placed on the intangible impacts, as these have largely been excluded from previous studies in the domain of PLFRA measures. Findings: – The framework provides a systematic way of assessing the costs and benefits of PLFRA measures. A unique feature of the framework is the inclusion of intangible impacts, such as anxiety and ill health, which are known to be difficult to measure. The study proposes to implement one of the stated preference methods (SPM) of valuation to measure these impacts, known as the willingness to pay method, as part of a survey of homeowners. The inclusion of these intangible impacts provides the potential to develop a more comprehensive understanding of the benefit cost ratio (BCR) for different stakeholders. The newly developed CBA conceptual framework includes four principal components: the tangible benefits to insurers; the tangible benefits to the government; the tangible benefits to homeowners; and the intangible benefits to homeowners. Originality/value: – This tool offers the potential to support government policy concerned with increasing the uptake of PLFRA measures through increasing the information available to homeowners and thereby supporting the decision-making process.